2021
DOI: 10.1080/08893675.2021.1951900
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic metaphors and personal meanings in group poetry therapy for people with schizophrenia

Abstract: This article concerns the therapeutic potential of metaphor in group poetry therapy, concentrating on the poetry therapy process of people diagnosed with schizophrenia. The data was collected in a one-year poetry therapy group. The main questions were: (1) What kind of therapeutic potential can metaphors offer in group poetry therapy? (2) What are the personal meanings and evaluations that the participants give to the therapy process and its effects on their lives? (3) What are the most significant elements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…According to the author's experience (see also Maanmieli & Ihanus, 2021), the use of haiku and tanka for therapeutic, rehabilitative, and preventive purposes has positive effects on advancing the well-being of the patients. At the same time, haiku and tanka therapy promotes and empowers fair culture, the realization of peoples' cultural rights and equal participation in the cultural activities of creating personal and communal meanings regardless of age, gender, language, disability, ethnicity, and religion.…”
Section: Haiku Therapymentioning
confidence: 99%
“…According to the author's experience (see also Maanmieli & Ihanus, 2021), the use of haiku and tanka for therapeutic, rehabilitative, and preventive purposes has positive effects on advancing the well-being of the patients. At the same time, haiku and tanka therapy promotes and empowers fair culture, the realization of peoples' cultural rights and equal participation in the cultural activities of creating personal and communal meanings regardless of age, gender, language, disability, ethnicity, and religion.…”
Section: Haiku Therapymentioning
confidence: 99%
“…s. 59) Runomuotoisille teksteille on tyypillistä, että niissä käytetään runsaasti metaforia, joiden avulla vaikeita asioita voi käsitellä turvallisesti ja sopivan etäältä. Poeettinen metafora voi olla silta tunteen ja ajatuksen välillä; se voi koskettaa jotain syvällä sisällämme, liikauttaa pintaamme (Ihanus 2019, 60;Maanmieli & Ihanus 2021).…”
Section: Kirjallisuusterapia On Luonnostaan Traumasensitiivinen Menetelmäunclassified
“…Elämykselliset metaforat voivat tarjota koskettavia ja mieleenpainuvia kokemuksia, ja niiden avulla terapeutin on mahdollista välttää liikaa ohjailua. (Moon 2017, 8-11;Maanmieli & Ihanus 2021. ) Palaamme metaforien terapeuttiseen käyttöön myöhemmin tässä artikkelissa rintasyövän sairastaneiden naisten ryhmän kuvauksessa.…”
Section: Kirjallisuusterapia On Luonnostaan Traumasensitiivinen Menetelmäunclassified
See 1 more Smart Citation
“…Related to the psychological influence of the world of words (poetry), Moon suggested that the interactive use of literature and therapeutic writing could be used to aid in healing schizophrenia, by utilizing metaphors to help find and create meaning in their lives (Maanmieli & Ihanus, 2021). Referring to the openness of poetry therapy, Mazza and Hayton state metaphors and symbols (in poetry) as important, which are similar to the symbolic components.…”
Section: Introductionmentioning
confidence: 99%